Clinical predictors of familial depression in Han Chinese women. - Wang, L; Qiao, D; Li, Y; Wang, L; Ren, J; He, K; Sun, J; Wang, Z; Tian, T; Chen, C; Yang, L; Hu, J; et al. (2012)
BACKGROUND: A number of clinical features potentially reflect an individual's familial vulnerability to major depression (MD), including early age at onset, recurrence, impairment, episode duration, and the number and pattern of depressive symptoms. However, these results are drawn from studies that have exclusively examined individuals from a European ethnic background. We investigated which clinical features of depressive illness index familial vulnerability in Han Chinese females with MD. METHODS: We used lifetime MD and associated clinical features assessed at personal interview in 1,970 Han Chinese women with DSM-IV MD between 30-60 years of age. Odds Ratios were calculated by logistic regression. RESULTS: Individuals with a high familial risk for MD are characterized by severe episodes of MD without known precipitants (such as stress life events) and are less likely to feel irritable/angry or anxious/nervous. CONCLUSIONS: The association between family history of MD and the lack of a precipitating stressor, traditionally a characteristic of endogenous or biological depression, may reflect the association seen in other samples between recurrent MD and a positive family history. The symptomatic associations we have seen may reflect a familial predisposition to other dimensions of psychopathology, such as externalizing disorders or anxiety states.